Correlation Between Neck Strength and Heading Performance in Male Football Players: Life Sciences-Physiotherapy - Abraham, Benji Kakkudiyil; Sathya, P.; Paul, Jibi; Vijaya Kumar, M. (International Journal of Life Science and Pharma Research, 2022)
Football, also known as soccer, is the world’s most popular sport, which involves multiple factors that consist of physiological, technical, tactical, mental and physical components. The technical skills involved in the game are juggling, speed dribbling, passing, shooting and heading. Repetitive impacts of the head to the ball have been shown to result in potential overload mechanism during the game. The injuries during heading are high when the head comes in contact with the elbow (41%) and headto- head impact (32%). The need and purpose of this study is to understand the correlation between neck muscle strength and heading performance in football players. The neck strength of the flexors and the extensors was assessed by the Baseline pushpull dynamometer and to test the heading precision, The Federation Internationale de Football Association Medical Assessment and Research Centre (F-MARC) test battery which is designed by The Federation Internationale de Football Association (FIFA) was selected. A total of 63 players were assessed and the results showed that a positive relationship is seen in the mean strength difference and the forward heading, and a positive relationship is seen in the mean strength difference and the right side heading. This study concludes that the neck extensors muscle strength and the neck flexors muscle strength are important for the heading performance in football players. Also, if the neck extensors strength is more than the neck flexors muscle strength, the heading performance was better.